Association between Oral Health and Mild Cognitive Impairment in Older Adults - Yordanis Garbey Pierre; Yudit Batista Delgado; Marlene Marina Gorguet Pi; Maria Eugenia Adjunta Medina (Editorial Ciencias Médicas, 2024)
Introduction: Along with the increase in the population of older adults, the prevalence of cognitive impairment is increasing. Recently, poor oral health has been introduced among potential risk factors. Objective: To determine the association between oral health and mild cognitive impairment in older adults in a community in the province of Santiago de Cuba. Methods: An observational, analytical and retrospective case-control study was carried out from January to July 2023. The study population consisted of 257 older adults living in this community, from which 40 cases were selected with a diagnosis of mild cognitive impairment, according to Petersen's criteria. Three controls were selected for each case, 120 older adults with approximately the same characteristics as the case. The strength of association of each risk factor was determined. Results: A significant association was found between having mild cognitive impairment and having 1 to 9 teeth. Oral pain was more frequent in 72.5% of the cases. Not remembering the last visit to the dentist was a cause of mild cognitive impairment in 42.5 %. Irregular brushing was 4.1 times more associated with the risk of developing this condition. Conclusions: There is an association between oral health and mild cognitive impairment in older adults. Having fewer teeth and reporting oral pain were important risk factors for cognitive impairment. Visiting the dentist and irregular tooth brushing had a negative influence on the disease. However, the use of dental prosthetics was a protective factor for mild cognitive impairment.